Analisa Tata Kelola Teknologi Informasi Pada Rumah Sakit Prima Inti Medika Menggunakan COBIT 2019 Dengan Skala Guttman - Pratama, Angga; rifqa, Rifqa; Ikhwani, Muhammad (STMIK Sinar Nusantara, 2025)
The development of technology and information is a crucial factor for companies to support the sustainability and success of business processes. In addition to utilizing information technology, companies must be able to manage and control the performance of the technology adopted through information technology governance (IT Governance). This is important to ensure that the technology implemented has a capability level that supports the achievement of business goals and organizational strategies. Prima Inti Medika Hospital has implemented Information Technology to provide the best service for patients and support business processes to achieve its goals. However, there has never been a comprehensive assessment of the capability level of information technology governance. This study measures the capability level of information technology governance at Prima Inti Medika Hospital using the COBIT 2019 standard. The research focuses on process objectives selected through design factor analysis, namely EDM03, BAI01, BAI02, BAI03, BAI04, BAI05, and BAI11. The results showed that only BAI11 reached the target capability level, namely level 4. While EDM03, BAI02, and BAI03 are at capability level 2, BAI01, BAI04, and BAI05 are at capability level 3. The gap analysis shows that the capability level of processes EDM03, BAI01, BAI02, BAI03, BAI04, and BAI05 states that activities are running but not fully implemented properly. Therefore, improvements are needed so that all activities are carried out properly to achieve the expected capability level.